2014
DOI: 10.1063/1.4879715
|View full text |Cite
|
Sign up to set email alerts
|

Experimental characterization of plasma formation and shockwave propagation induced by high power pulsed underwater electrical discharge

Abstract: High power pulsed electrical discharges into liquids are investigated for new industrial applications based on the efficiency of controlled shock waves. We present here new experimental data obtained by combination of detailed high speed imaging equipments. It allows the visualization of the very first instants of plasma discharge formation, and then the pulsations of the gaseous bubble with an accurate timing of events. The time history of the expansion/compression of this bubble leads to an estimation of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 5 publications
0
11
0
Order By: Relevance
“…A GAP with metal electrodes is always used to transfer high-pulsed current, and is commonly used in pulsed power facilities, such as high-power spark gap switches [1]- [4], electrohydraulic cleaning [5], environmental applications [6], electrical-discharge machining [7], etc. Electrode erosion is one of the key factors that restrict the development of the above applications.…”
Section: Introductionmentioning
confidence: 99%
“…A GAP with metal electrodes is always used to transfer high-pulsed current, and is commonly used in pulsed power facilities, such as high-power spark gap switches [1]- [4], electrohydraulic cleaning [5], environmental applications [6], electrical-discharge machining [7], etc. Electrode erosion is one of the key factors that restrict the development of the above applications.…”
Section: Introductionmentioning
confidence: 99%
“…ere are many researchers investigating the characteristics of WSWs produced by HVPD [12][13][14][15][16][17][18][19], but few of them considered the effects of P H on WSWs. Furthermore, other researchers carried out some experiments to study the electrical characteristics of pulsed discharge in pressurized water [20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…The changed solution color probably indicated that the carbon solid materials were formed from the glycine degradation reaction while applying the high-voltage discharge plasma. Even though the reason why the carbon solid materials were only generated under high-pressure conditions is not clear yet, as described above, when the high-voltage discharge plasma was applied in the gas-liquid water environment, the physical and chemical effects, i.e., shock wave generation, strong electrical field, ultraviolet radiation, and diverse radicals generation, may happen simultaneously [6,7,[11][12][13][14][15][16][17]96,97]. The reactive chemical species that have high reactivity, i.e., hydrogen peroxide molecules, hydrogen molecules, oxygen molecules, and hydroxyl radicals, may interact and react with the glycine compound.…”
Section: Resultsmentioning
confidence: 99%
“…Hence, discharge plasma in a gas-liquid water environment is considered one of the most promising technologies that can be applied in various fields, i.e., water pollutant removal, biological inactivation, polymer surface modification, chemical synthesis, and nanoparticle synthesis [6][7][8][9][10]. In addition to the chemical effects, the discharge plasma in the gas-liquid water environment also results in physical effects, i.e., ultraviolet radiation and shockwave Plasma 2021, 4 310 generation [6,7,[11][12][13][14][15][16][17]. Another advantage regarding the use of discharge plasma in the gas-liquid water environment is that the discharge plasma is usually more easily formed in the gas phase than in the liquid state.…”
Section: Introductionmentioning
confidence: 99%